EFEKTIFITAS PENILAIAN MENGGUNAKAN DATA CEK DAN SKALA RENTANG PADA MATA PELAJARAN FIQIH BAB WUDHU KELAS VII MTs TQ EL MUNA Q - nashrullahzaki; Wahyu Kholis Prihantoro; Nisaul Khoiriyyah; Rodhotul Jannah; Rahma Santika; Imam Musyafa (Kreatifitas Jurnal Ilmiah Pendidikan Islam, 2025)
This study aims to describe and compare the effectiveness of three models for assessing ablution practices in seventh-grade students of MTs TQ El Muna Q: global assessment, checklist, and scale assessment. This study used a descriptive qualitative approach with observation, interviews, and literature review methods. The subjects included Islamic Religious Education teachers and nine seventh-grade students. The instruments used were a checklist observation sheet containing 16 aspects of the pillars and sunnah of ablution and a scale assessment sheet with a scale of 1–4 that assessed five main aspects of the skill. The results showed that global assessment was practical but less accurate because it did not indicate specific student errors. Assessment using a checklist provided the most detailed results and helped teachers and students clearly identify errors. Meanwhile, the scale assessment provided an objective and easily analyzed picture of the quality of ablution implementation, especially aspects of calmness, neatness, and efficiency of water use. The combination of a checklist and scale assessment proved to be the most effective because it assessed both technical aspects and students' overall worship attitudes.